No increased incidence of venous thrombosis or pulmonary embolism after SARS-CoV-2 vaccination in Germany. (June 2022) - Tanislav, C.; Rosenbauer, J.; Zingel, R.; Kostev, K.
Abstract: Objectives: Vaccination is one of the most effective measures to combat the COVID-19 pandemic. The main reason for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination hesitancy is the potential side-effects. This study aimed to investigate the incidence of venous thrombosis and pulmonary embolism in patients who received SARS-CoV-2 vaccination. Study design: This was a retrospective cohort study. Methods: Individuals aged ≥18 years who received an initial vaccination for COVID-19 in one of 1134 general practices in Germany between April and June 2021 were included in the study. Vaccinated patients were matched to unvaccinated individuals by age, sex, index month (April to June 2020 [unvaccinated cohort] or April to June 2021 [vaccinated cohort]) and diagnoses that may be associated with an increased incidence of thrombosis documented within 12 months before the index date. The incidences of thrombosis and non-fatal pulmonary embolism as a function of COVID-19 vaccination were analysed. Results: The present study included 326, 833 individuals who were vaccinated against COVID-19 and 326, 833 matched unvaccinated individuals. During the follow-up period, 406 vaccinated patients and 342 individuals in the control group received a diagnosis of thrombosis or non-fatal pulmonary embolism. This resulted in an incidence rate of 11.9 vs 11.3 cases per 1000 patient-years for vaccinated vs unvaccinated individuals, respectively, and a non-significant overall incidence rate ratio (IRR: 1.06; 95% confidence interval [CI]: 0.93–1.22). The highest IRR was observed in the 41–60 years age group (IRR: 1.30; 95% CI: 0.98–1.73), and the lowest IRR was seen in the 18–40 years age group (IRR: 0.6; 95% CI: 0.0–1.05); however, none of the individual age group incidence rates was significant. Conclusions: The results indicate that the occurrence of thrombosis or pulmonary embolism after COVID-19 vaccination is a coincidental finding rather than a consequence of vaccination.